Knowledge Integration Model of Blockchain Technology in Higher Learning Institutions: A Rasch Measurement Model Approach for Pilot Study - Nur Ilyana Ismarau Tajuddin; Nurafifah Mohd Nor; Nor Aziyatul Izni; Nur Idayu Ah Khaliludin; Aeshah Mohd Ali (Usim Press, 2026)
Indexed by MyCite